Tɨnuango moniya uai: anastasia candre yamacuri’s word of wealth (2014)
This paper expands on the concept of moniya uai in a threefold manner: as a critique of the hegemonic culture, as a research method, and as a creative process. We believe these three phases can be found in the poetic and pictorial work of the uitoto-okaina writer and researcher Anastasia Candre Yamacuri.